2021
DOI: 10.1016/j.jogc.2020.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs and Perspectives of Women and Obstetrical Providers in Northern Ontario on Water Births

Abstract: Objective: This study sought to understand the beliefs and perspectives of women in northern Ontario and their obstetrical providers with respect to water birthing as access to this service is limited in this region Methods: All midwives, family physicians (FPs), and obstetricians providing labour and delivery services in northern Ontario were surveyed, as were a sample of labour and delivery nurses in the region and convenience samples of regional women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Since that time, studies have documented the safety of water birth, the benefits, and the relative absence of risk in low-risk pregnancies without a revision of the ACOG statement 17–19. A Canadian study reveals the depth of the divide between interest in water birth and a broader implementation of the practice 20. A survey of 362 women found 81.8% thought water births were safe, 76.5% wanted the option of a water birth, and 40.9% were interested in a water birth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since that time, studies have documented the safety of water birth, the benefits, and the relative absence of risk in low-risk pregnancies without a revision of the ACOG statement 17–19. A Canadian study reveals the depth of the divide between interest in water birth and a broader implementation of the practice 20. A survey of 362 women found 81.8% thought water births were safe, 76.5% wanted the option of a water birth, and 40.9% were interested in a water birth.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] A Canadian study reveals the depth of the divide between interest in water birth and a broader implementation of the practice. 20 A survey of 362 women found 81.8% thought water births were safe, 76.5% wanted the option of a water birth, and 40.9% were interested in a water birth. Midwives and physicians were diametrically opposed.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 3898 records were obtained from the seven electronic databases and relevant citation searching. After the exclusion of 1288 duplicates and 2523 irrelevant titles/abstracts, 88 full texts were examined and 22 papers such as unpublished dissertations (n = 4) (Mercredi, 2020;Russell, 2016;Way, 2015;Woodward, 2012) and peer-reviewed journal articles (n = 18) (Al Moghrabi, 2023;Bolsoy et al, 2022;Cooper et al, 2018Cooper et al, , 2019Cooper et al, , 2021Kaur & Singh, 2019;Lewis, Hauck, Butt, et al, 2018;Meyer et al, 2010;Milosevic et al, 2019Milosevic et al, , 2020Newnham et al, 2015Newnham et al, , 2017Nicholls et al, 2016;Orrantia & Petrick, 2021;Plint & Davis, 2016;Russell et al, 2014;Stark & Miller, 2009;Ulfsdottir et al, 2020) were included in this review. Search outcomes are displayed using the PRISMA flow diagram (Figure 1).…”
Section: Search Outcomementioning
confidence: 99%
“…This aligns with research of health practitioners' attitudes to waterbirth in Ontario, Canada. Within this research there was a universal finding that none of the obstetricians surveyed would consider assisting with or offering hospital-based water birth in the future, whereas 97% of midwives and half of general practitioners surveyed would consider this (Orrantia & Petrick, 2021). The obstetricians in this Canadian research had the perception of greater risks with water birth than consumers, midwives or general practitioners.…”
Section: Water Immersion In Labourmentioning
confidence: 82%
“…Pools for water immersion are less available within obstetric birth settings which maintains this lack of familiarity and confidence for staff and the literature supports that hospital staff, both midwives and obstetricians, operate as gate keepers to pool use (Milosevic et al, 2020;Russell, 2011). While some birthing suite midwives have indicated that they believe water immersion has an important role within obstetric birth settings this belief was not held by obstetricians who did not want to and were not confident in providing care for women using water immersion (Orrantia & Petrick, 2021;Plint & Davis, 2016).…”
Section: Institutional Views Of Risk and Water Birthmentioning
confidence: 99%